Influence of Dilation Angle of Soil on Seismic Displacements of Gravity Retaining Walls using Upper Bound Limit Analysis Method - P. Sharifi; O. Farzaneh; F. Askari (Numerical Methods in Civil Engineering)
In this paper, permanent displacements of gravity retaining walls with back and front fill under seismic excitation due to sliding is investigated. In this regard, by using the upper bound theorem of limit analysis, an expression is presented for obtaining the yield acceleration coefficient and also, critical angles of failure wedges are calculated. Several comparisons are made with other solutions in literature. Effect of variation of dilation angle and ratio of the height of front fill to backfill soil is evaluated on seismic performance of a gravity retaining wall. Results showed that by increasing dilation angles from zero to internal friction angle of the soil, the values of seismic displacement inclines.